Which Duality? Why Dual? On the Gains and Losses of Hungarian Sociology’s Dual-society Theories (Szociológiai Szemle, 2023)
Hungarian sociology is abundant in dual-society and dual-structure theories. In most cases the mentioned duality is not the same. In my paper – to answer the question of which duality? – I compile a catalogue of Hungarian sociology’s dual-structure and -society theories. As a follow-up step – this time while trying to answer the Why dual? question – I associate Hungarian sociology’s dual-society images with Hungarian society’s East-Central European semi-peripheral status. I propose that the semi-periphery of the capitalist world-system as a historically formed mode of existence is not evadable in its effects and lays the tendencies out for the cognition of this mode of existence. As a structural constraint it conditions Hungarian sociology to ”recognize” the dualities of the social-structure. Finally, I argue for going beyond these duplicating strategies.